Development of test instruments to measure high level thinking ability of two linear variable equations system - Anggit Prabowo; Puspa Puspa; Fariz Setyawan (International Journal on Education Insight, 2021)
This study aims to develop a test instrument to measure the high-level thinking ability of the two-variable linear equation system material. This research is a Research and Development using the ADDIE development model consisting of steps of analysis, design, development, implementation, and evaluation. The test subjects in this study were students of class VIII of SMP Negeri 3 Payung. The instruments used in this study were validation sheets and documentation. Data collection techniques through expert judgment and tests. This research has succeeded in developing a test instrument to measure the high-level thinking ability of two-variable linear equations system material. The test developed consists of 10 multiple choice items and 5 description items that have been declared valid by expert judgment. The trial results show from the difficulty index analysis of multiple-choice questions was obtained as much as 1 item in the easy category, 9 questions in the moderate category, the analysis of the difficulty index for the essay obtained by 2 items in the medium category, 3 questions in the difficult category. In the analysis of discriminant index of multiple-choice questions, there were 1 question in the bad category, 3 questions with enough categories, and 6 questions in the good category. In the analysis of the difference in power, 2 questions were categorized as bad, 1 question was categorized as sufficient, 2 questions were categorized as good. Based on the analysis of the function of the distractor, it was found that 1 question was not functioning properly, 9 questions were functioning properly. Finally, from the reliability analysis, it was obtained 0.73 for multiple choice questions and 0.716 for essay questions with high reliability interpretation.